Analysis of the impact of augmented reality on learning in times of pandemic (LACCEI, 2024)
Information and communication technologies (ICT) have played an important role in society, affecting almost every aspect of our lives. In the educational field, ICT revolutionizes the teaching and learning experience, and helps one of the greatest challenges that arise in the classroom, education. Different technologies have been applied in this area, such as Video Modeling (MV), Serious Games (JS) and Gamification but one of the most effective are emerging immersive technologies such as Augmented Reality (AR). A systematic review of the literature (RSL) of the studies of AR in student learning was carried out. The search strategy adopted identified 116,420 studies, of which 104 were selected as primary studies. The studies selected for the RSL helped answer 8 research questions posed for this study. The results of the RSL have concluded predominant trends in the research and applications of AR in learning, the areas of knowledge where AR is used and the areas that use AR.